SCALE DEVELOPMENT FOR MEASURING THE FARMERS’ ATTITUDE TOWARDS SUSTAINABLE AGRICULTURAL PRACTICES - BIDYAPATI THANGJ; K. K. JHA; SAURABH SHARMA (The Journal of Research ANGRAU, 2024)
This study was conducted in Manipur in the year 2021-2022 to create an attitude scale for measuring of farmers’ attitudes towards sustainable agricultural practices in the state. In the procedure of the scale construction, after editing and modifying the statements 68 statements were sent to 55 experts for relevancy test. Out of this 27 experts responded, and the statements with a relevancy percentage (>75), relevancy weightage (>0.75), and mean relevancy score (>2.30) were included in the analysis of item for the statement. Altogether, item analysis included 25 statements. The statements were allotted to 27 farmers from a non-sampling area to specify their degree of favourable and unfavourable of each statement on five continuum. Based on the criterion groups t value was calculated for each item, and statements were selected with a “t” value greater than or equal to 1.75. The final scale comprised of 13 statements among which 8 were positive and 5 were negative. Moreover, these statements demonstrated strong reliability and validity, supported by a correlation coefficient of 0.71, indicating their robustness. This validated instrument will be used to gauge farmers’ attitudes towards adopting sustainable agricultural practices.